Pengaruh Pembelajaran PAK Terhadap Perubahan Sikap Siswa Kelas V dan VI di SD Katolik 2 St. Joseph Woloan - Imbang, Jearne Felix; Kohom, Yulita Hermina; Tuerah, Glendhy Christian (Sekolah Tinggi Pastoral Don Bosco Tomohon, 2024)
Learning is a process in which individuals acquire new knowledge, skills, values, or attitudes through experience, teaching, or training. Catholic Religious Education (PAK) is considered a means of increasing religious understanding and forming students' social attitudes towards their surrounding environment, including parents, friends and teachers at school. This research aims to explore the influence of PAK Learning on Changes in Attitudes of Class V and VI Students at St. Catholic 2 Elementary School. Joseph Woloan. The research population consisted of 61 students in grades V and VI who were active members of the school. A sample of 53 students was determined using the Slovin formula to produce representative generalizations. The main instrument used was a questionnaire with 30 statements, distributed directly to the selected sample. The collected data was analyzed using the IBM SPSS 25 for Windows application. The research results show that PAK learning has a significant influence in shaping students' attitudes, with a contribution of 81% to the observed attitude changes. This shows that this learning program plays an important role in shaping and directing students' attitudes in accordance with the values ​​taught.